Pancakarsa and Fiscal Clientelism in Bogor Regency: Navigating Religious Populism and the Shadow State - Aep Saepudin Muhtar; Gotfridus Goris Seran; Faisal Tri Ramdani; Cecep Wahyudin; Dede Syafrudin; Irma Purnamasariv; Neng Virly Apriani; Radif Khotamir Rusli (Lembaga Bale Literasi, 2025)
This article critically examines fiscal clientelism in Bogor Regency through the Pancakarsa vision-mission framework and its five governmental commitments: Bogor Cerdas, Bogor Sehat, Bogor Maju, Bogor Berkeadaban, and Bogor Nyaman. Drawing on shadow-state theory, the study explores how informal political actors—including brokers, financiers, business elites, intellectuals, religious leaders, and political families—shape project allocation, strategic appointments, licensing, and patron-client reciprocity within local democratic institutions. The article argues that Pancakarsa can operate as a democratic governance grammar only when its programmatic commitments are insulated from clientelistic brokerage and translated into transparent budgeting, civic literacy, participatory oversight, and pluralist religious communication. Employing qualitative conceptual-policy analysis and thematic interpretation of governance documents, policy discourse, and recent scholarly literature, the study shows that fiscal legitimacy is not merely a matter of administrative compliance, but a contested political resource through which voters evaluate distributive fairness, institutional credibility, and moral leadership. The findings contribute to debates on Indonesian local democracy by demonstrating how fiscal-voter strategy can either reproduce shadow-state domination or strengthen democratic resilience when anchored in accountable public finance and inclusive civic education. The article offers policy implications for designing anti-clientelistic procurement, open budgeting, transparent appointments, digital complaint systems, and pluralist communication strategies in Bogor Regency and comparable decentralized settings